1999
DOI: 10.1093/clinchem/45.6.777
|View full text |Cite
|
Sign up to set email alerts
|

Strand Displacement Amplification and Homogeneous Real-Time Detection Incorporated in a Second-Generation DNA Probe System, BDProbeTecET

Abstract: Background: Amplified DNA probes provide powerful tools for the detection of infectious diseases, cancer, and genetic diseases. Commercially available amplification systems suffer from low throughput and require decontamination schemes, significant hands-on time, and specially trained laboratory staff. Our objective was to develop a DNA probe system to overcome these limitations. Methods: We developed a DNA probe system, the BDProbeTecTMET, based on simultaneous strand displacement amplification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(40 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…100% for detection of C. trachomatis and N. gonorrhea nucleic acid 145 while another reported a specificity of 99.2% and sensitivity of 99.3% for N. gonorrhoea using BD ProbeTec TM SDA system on urine samples, in which results were obtained in less than 5 hrs with better performance than culture method. 152 Similarly, Van Der Pol et al- 153 reported sensitivity ranging from 80.5% to 98.5% when this assay was used to detect chlamydia and gonorrhoea infection in men and women using urine, cervical and urethral swabs.…”
Section: Strand Displacement Amplification (Sda)mentioning
confidence: 98%
See 2 more Smart Citations
“…100% for detection of C. trachomatis and N. gonorrhea nucleic acid 145 while another reported a specificity of 99.2% and sensitivity of 99.3% for N. gonorrhoea using BD ProbeTec TM SDA system on urine samples, in which results were obtained in less than 5 hrs with better performance than culture method. 152 Similarly, Van Der Pol et al- 153 reported sensitivity ranging from 80.5% to 98.5% when this assay was used to detect chlamydia and gonorrhoea infection in men and women using urine, cervical and urethral swabs.…”
Section: Strand Displacement Amplification (Sda)mentioning
confidence: 98%
“…The displaced strands then form the template for subsequent amplification which culminate to more rapid target amplification. 24,143 SDA product detection is possible by methods such as gel electrophoresis, [144][145][146] molecular beacons 145,147 and fluorescence methods. [148][149][150] SDA has been applied in the diagnosis of tuberculosis through reverse-transcriptase SDA.…”
Section: Strand Displacement Amplification (Sda)mentioning
confidence: 99%
See 1 more Smart Citation
“…This method is an isothermal template amplification technique that can be used to detect trace amounts of DNA or RNA of a particular sequence (Becton Dickinson and Company, Sparks, MD). In its current format, strand displacement amplification occurs in two phases, target generation and exponential target amplification [22].…”
Section: Strand Displacement Amplificationmentioning
confidence: 99%
“…1 These disadvantages have limited its application to some special elds such as point-ofcare use in resource-limited areas. 2 In an effort to reduce the resource requirements of PCR, a variety of isothermal amplication techniques have been developed and applied widely, including self-sustained sequence replication reaction (3SR), 3 rolling circle amplication (RCA), 4 strand displacement amplication (SDA), 5 helicasedependent amplication (HDA), 6 loop-mediated isothermal amplication (LAMP) 7 and recombinase polymerase amplication (RPA), 8 Cross-priming amplication (CPA), 9 and Polymerase Spiral Reaction (PSR), 10 etc. 3SR, NASBA, SDA, HDA and RPA, require multiple enzymes and rigorous optimization, which may increase the assay cost.…”
Section: Introductionmentioning
confidence: 99%